ChemInform Abstract: Synthesis of Isatins by the Palladium‐Catalyzed Intramolecular Acylation of Unactivated Aryl C(sp2)—H Bonds. Issue 17 (April 2016) - Li, Jue; Zheng, Yang; Yu, Xinling; Lv, Songyang; Wang, Qiantao; Hai, Li; Wu, Yong
Abstract: Using air as the oxidant, the PdCl2 ‐catalyzed intramolecular cyclization of N‐alkylglyoxalanilides gives the corresponding isatins in good to high yields.